Investigation Of Free-Flow Speed At Basic Segment Expressways For Level Terrain In Malaysia - Muhammad, Hazwaruaida (2014)
Free-flow speed (FFS) is an important parameter in the speed-flow relationship, analyses of capacity and level of service (LOS) for basic segment expressways. Relevant authorities in Malaysia have been referring to the ArahanTeknik (Jalan) 8/86 to estimate LOS for basic segment expressways based on v/c ratio. However, due to the technological advancement and the surge of vehicle numbers on roads, the values obtained in the study may not show the actual resemblance of current Malaysian traffic conditions in Malaysia. There are several FFS models presented in major references and previous studies throughout the world. However, the suitability of these models for Malaysian traffic conditions is limited to some extent. Therefore, this study was conducted to understand in more detail about FFS at basic segment expressways and to develop FFS model based on current local standards. Six FFS models are developed based on regression analysis. However, one final model is selected as the best FFS model through the performance indicators. In this study, FFS of vehicles without motorcycles using headway (≥ 8 s) is selected as the best FFS model. Sensitivity analysis had also been performed in order to measure the sensitivity of each parameter for the developed FFS model. Thus, the outcome of this study is valuable for local traffic engineers and highway authorities in Malaysia for better understanding of the FFS and to estimate LOS at basic segment expressways.